Hot corrosion of Fe and Ni-based alloys in Wase-to-energy environment at 850 °C. (March 2022) - Sun, Haofei; Liu, Jing
Highlights: Cr2 O3 is the main phase to protect alloys at 850 °C. Operating temperature and exposure time are two critical factors for formed oxides. Traditional CRAs are not recommended in WTE environment. Abstract: Boiler tube alloys in waste-to-energy (WTE) facilities suffer from significant corrosion, induced by metal chlorides and sulfates at high temperatures. This work aims to explore the effects of alloying elements (Ni and Cr) on the hot corrosion of boiler tube alloys, and clarify the role of elevated temperature and service time on their protective and failure mechanisms. Long-term hot corrosion experiments were performed on three typical corrosion resistance alloys (CRAs, including Inconel 625, 310S, and 00Cr30Mo2) in simulated WTE salts at 850 °C. Results confirmed that Cr2 O3 is the main phase for corrosion protection of these alloys at 850 °C. The greatest hot corrosion resistance is demonstrated by 00Cr30Mo2, due to its highest Cr content among these three CRAs. Although the measured corrosion rates are all lower than the conventional "acceptable" corrosion rate of 1 mm/yr., the estimated penetration rates of these alloys range from 1.58 to 8.50 mm/yr. Therefore, none of the selected CRAs can be recommended for the WTE environment at 850 °C. Operating temperature and exposure time are also confirmed as two critical factors for the formed oxides, influencing the protective mechanism and corrosion behaviour. In addition, hot corrosion mechanisms of all alloys were revealed with the support of cross-sectional SEM and EDS analysis.